Comparison of different treatment planning approaches using VMAT for head and neck cancer patients with metallic dental fillings - Liugang Gao; Chunying Li; Zhengda Lu; Kai Xie; Tao Lin; Jianfeng Sui; Xinye Ni (Radiation Medicine and Protection, 2021)
Objective: To explore treatment planning approaches using volumetric modulated arc therapy (VMAT) for head and neck cancer patients with metallic dental fillings. Methods: Fifty-six patients with metallic dental fillings treated with radiotherapy were selected, and three VMAT plans, the jaw-tracking plan, fixed-jaw plan, and non-coplanar plan, were designed for each patient. In the jaw-tracking plan, two coplanar partial arc fields that avoid the metal area were set, and the jaw was automatically tracked. In the fixed-jaw plan, different fields were set in three sections according to the fixed-jaw method. The fields were the same as those in the jaw-tracking plan for the section containing metal implants, while full arc fields were set in the nonmetal sections. In the non-coplanar plan, a non-coplanar arc field was added based on the jaw-tracking plan. The treatment plan in the jaw-tracking plan was optimized, and the constraints on the planning target volume (PTV) or organs at risk (OARs) in the jaw-tracking plan were copied to the other two plans. The dose distribution in PTV and OARs of the patients in the three treatment plans was compared. Results: There were no significant differences in the maximum doses to the spinal cord or optic nerves among the three treatment plans. However, compared with the jaw-tracking plan, the fixed-jaw plan showed lower mean doses to the pharynx [(42.9 ​± ​7.1) Gy vs. (44.1 ​± ​7.1) Gy, P ​< ​0.05] and larynx [(43.9 ​± ​3.9) Gy vs. (45.4 ​± ​4.7) Gy, P ​< ​0.05], while the non-coplanar plan obtained significantly better dose distribution in PTV and all OARs except for the spinal cord and optic nerves. Meanwhile, the non-coplanar plan performed significantly better than the fixed-jaw plan in terms of the maximum doses to the brainstem [(50.2 ​± ​4.0) Gy vs. (51.4 ​± ​4.6) Gy, P ​< ​0.05], left lens [(5.8 ​± ​0.2) Gy vs. (6.3 ​± ​0.4 ​Gy), P ​< ​0.05], and right lens [(5.9 ​± ​0.3) Gy vs. (6.2 ​± ​0.3) Gy, P ​< ​0.05]. Conclusions: The non-coplanar VMAT is an optimal method for treating head and neck cancer patients with metallic dental fillings since it can provide better dose distribution in PTV and reduce doses to OARs.